Strategi Buddhis Mengatasi Kemarahan - Kajian Analisis Berdasarkan Sutta Pitaka - Medhacitto, Tri Saputra; Sukhitta Dewi (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2024)
This research aims to discover the Buddhist strategies for dealing with anger based on Buddha’s teachings as presented in the Sutta Pitaka. This research is qualitative research with a library approach. The research was carried out in three steps, namely: 1) Esanā or step of data collection, namely by collecting information from the Pali Canon or books, journals, articles that are relevant to the research topic; 2) Vimaṃsā or data analysis by means of data reduction, data presentation, and drawing conclusions; 3) Anubodha or step of drawing conclusion to answer the research objectives. This research shows that anger is a negative emotion that brings negative impacts on an individual and social life. The emotion of anger can appear in the form of hatred (dosa), ill will (byāpāda), aversion (paṭigha), anger (kodha), and conflict (āghāta). The Buddha’s teachings contained in the Sutta Pitaka can be a strategic solution for dealing with anger. The Paṭhamaāghātapaṭivinaya Sutta and Vitakkasaṇṭhāna Sutta offer strategic solutions for dealing with anger in accordance with Buddha’s teachings. Thus, Buddha’s teachings can be applied as a practical guide for dealing with anger in daily life.